Health System Capacity and Access Barriers to Diagnosis and Treatment of CVD and Diabetes in Nepal - Abhishek Sharma; Warren A. Kaplan; Gautam Satheesh; Indra Prasad Poudyal; Pawan Gyawali; Dinesh Neupane; Parash Mani Bhandari; Milan Malla; Surendra Sapkota; Shiva Raj Mishra (Ubiquity Press, 2021)
Background: Universal access to essential medicines and routine diagnostics is required to combat the growing burden of cardiovascular disease (CVD) and diabetes. Evaluating health systems and various access dimensions - availability, affordability, accessibility, acceptability, and quality - is crucial yet rarely performed, especially in low- and middle-income countries. Objective: To evaluate health system capacity and barriers in accessing diagnostics and essential medicines for CVD and diabetes in Nepal. Methods: We conducted a WHO/HAI nationally-representative survey in 45 health-facilities (public sector: 11; private sector: 34) in Nepal to collect availability and price data for 21 essential medicines for treating CVD and diabetes, during May-July 2017. Data for 13 routine diagnostics were obtained in 12 health facilities. Medicines were considered unaffordable if the lowest paid worker spends >1 day's wage to purchase a monthly supply. To evaluate accessibility, we conducted facility exit interviews among 636 CVD patients. Accessibility (e.g., private-public health facility mix, travel to hospital/pharmacy) and acceptability (i.e. Nepal's adoption of WHO Essential Medicine List, and patient medication adherence) were summarized using descriptive statistics, and we conducted a systematic review of relevant literature. We did not evaluate medicine quality. Results: We found that mean availability of generic medicines is low (<50%) in both public and private sectors, and less than one-third medicines met WHO's availability target (80%). Mean (SD) availability of diagnostics was 73.1% (26.8%). Essential medicines appear locally unaffordable. On average, the lowest-paid worker would spend 1.03 (public sector) and 1.26 (private sector) days' wages to purchase a monthly medicine supply. For a person undergoing CVD secondary-prevention interventions in the private sector, the associated expenditure would be 7.5-11.2% of monthly household income. Exit interviews suggest that a long/expensive commute to health facilities and poor medicine affordability constrain access. Conclusions: This study highlights critical gaps in Nepal's health system capacity to offer basic health services to CVD and diabetes patients, owing to low availability and poor affordability and accessibility. Research and policy initiatives are needed to ensure uninterrupted supply of affordable essential medicines and diagnostics.